2012
DOI: 10.2147/copd.s28602
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of chronic obstructive pulmonary disease: a descriptive study in the mid-western region of Nepal

Abstract: BackgroundThe purpose of this study was to analyze the distribution of chronic obstructive pulmonary disease (COPD) in terms of time, place, and person among inpatients at the Mid Western Regional Hospital (MWRH) in Nepal.MethodsA descriptive cross-sectional study was carried out by analyzing trends using secondary data for the fiscal years 2006–2009 in the inpatient department of the MWRH.ResultsThe majority of patients admitted for treatment of COPD were women (60%) and from higher ethnic groups (having a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 6 publications
8
56
0
1
Order By: Relevance
“…Several previous studies showed that most of the COPD patients belonged to the age group 40-65 years which was in agreement with the present study 10,11 . More than half of COPD burden were borne by females supporting the fact that most of the COPD patients are females as they are exposed to indoor biomass fuel fi res for considerably long period of time 10,12 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Several previous studies showed that most of the COPD patients belonged to the age group 40-65 years which was in agreement with the present study 10,11 . More than half of COPD burden were borne by females supporting the fact that most of the COPD patients are females as they are exposed to indoor biomass fuel fi res for considerably long period of time 10,12 .…”
Section: Discussionsupporting
confidence: 94%
“…Several previous studies showed that most of the COPD patients belonged to the age group 40-65 years which was in agreement with the present study 10,11 . More than half of COPD burden were borne by females supporting the fact that most of the COPD patients are females as they are exposed to indoor biomass fuel fi res for considerably long period of time 10,12 . World health organization (WHO) estimated that 22 percent of all COPD cases are caused by the indoor smoke from biomass fi res and this study supports this statement as majority of COPD clients were involved in household activities and more than half of them reported of using biogas fuel for cooking similar to the study done at Mid-Western Regional Hospital of Nepal 1,10 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…5 This can be co-related with the study, which depicted the extensive use of biomass fuels by female individuals for long period of time increased the risk of indoor air pollution. 6 Several other studies presented similar findings where females are predominantly affected. [6][7][8][9] According to the WHO, previously COPD was more common in men while because of increased tobacco use among females in high-income countries and the extensive exposure to indoor biomass fuels used for cooking and heating in low-income countries, both genders are almost equally affected by the disease.…”
Section: Antibiotics Use Patternsupporting
confidence: 57%
“…6 Several other studies presented similar findings where females are predominantly affected. [6][7][8][9] According to the WHO, previously COPD was more common in men while because of increased tobacco use among females in high-income countries and the extensive exposure to indoor biomass fuels used for cooking and heating in low-income countries, both genders are almost equally affected by the disease. 10 However, some studies showed the higher prevalence of male suffers than the women because of increased frequency of smoking among men.…”
Section: Antibiotics Use Patternsupporting
confidence: 57%